2006
DOI: 10.1002/ceat.200500377
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Predictions of Physical Properties – Prediction of Solid Solutions in Molecular Solutes Exhibiting Polymorphism

Abstract: Polymorphism is a widespread phenomenon among molecular components, and usually the lattice energies of the different varieties are rather close. It is shown that solid solutions, by means of insertion (e.g., due to solvent) or by means of substitution (e.g., due to derivatives of the components), can substantially modify the energy landscape between polymorphs. Fluctuations in the transition temperatures lead to the prediction of the existence of solid solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…This is a kinetic phenomenon with the additive generating faster growing nuclei of the metastable form or inhibiting the growth of the nuclei of the stable form. Additives can apparently overturn the order of stability of the polymorphs through solid solution formation 42. A number of studies have demonstrated the effect of additives43 in stabilizing a kinetic form, or inhibiting the production of one form at the expense of another 44, 45.…”
Section: Discussionmentioning
confidence: 99%
“…This is a kinetic phenomenon with the additive generating faster growing nuclei of the metastable form or inhibiting the growth of the nuclei of the stable form. Additives can apparently overturn the order of stability of the polymorphs through solid solution formation 42. A number of studies have demonstrated the effect of additives43 in stabilizing a kinetic form, or inhibiting the production of one form at the expense of another 44, 45.…”
Section: Discussionmentioning
confidence: 99%
“…Even after three years, the γ form of PZA remains unchanged when it is spray dried with DMU, while it transforms within 1 week without DMU. The minimal amount of DMU required in the starting mixture to increase the lifetime of γ-PZA is about 5 mass %, as was determined by Baaklini et al 16 Powder X-ray diffraction (PXRD) showed no sign of the formation of a cocrystal, whereas the binary phase diagram and Tammann plot of γ-PZA and DMU-I revealed no indication of a partial solid solution 26 , 27 at the extremes of the phase diagram. 24 The binary phase diagram and Tammann plot of γ-PZA with DMU-I are also included as Supporting Information for this work.…”
Section: Introductionmentioning
confidence: 71%
“…Moreover, this two forms lead to a solid solution with Phenanthrene in a very small concentration range. This case would be remarkable as it should induce an increasing of the polymorphic transition temperature from at least 80°C [8].…”
Section: -P2mentioning
confidence: 99%
“…In the field of organic materials, and more particularly of Active Pharmaceutical Ingredients (APIs), the chemical and structural purities are critical in the development of an API [1]. Melt crystallization [2], especially the zone melting technique, is sometime used to access to very high pure materials or even 'ultra-pure' (purity greater than 99.9%).…”
Section: Introductionmentioning
confidence: 99%